Presidential Decree-Law No. 119 Of The Year 2014 Concerning The Suez Canal Investment And Development Certificates = في شأن شهادات استثمار وتنمية قناة السويس - Egypt; The middle east library for economic services, translator. (2025)
Presidential decree-law no. 119 of the year 2014 concerning the Suez Canal investment and development certificates قرار رئيس جمهورية مصر العربية بالقانون رقم 119 لسنة 2014 فى شأن شهادات استثمار وتنمية قناة السويس